Performance degradation and microstructure changes in freeze-thaw cycling for PEMFC MEAs with various initial microstructures - Lee, Sang-Yeop; Kim, Hyoung-Juhn; Cho, EunAe; Lee, Kug-Seung; Lim, Tae-Hoon; Hwang, In Chul; Jang, Jong Hyun (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
When the temperature of a fuel cell vehicle is repeatedly reduced to subzero temperatures volume changes by water/ice transformations and frost heave mechanism can cause microstructural changes in membrane electrode assemblies (MEA), and a resultant permanent decrease in the performance of fuel cell stacks In this study five MEAs manufactured by different methods were tested under repeated freeze-thaw (F-T) cycles between -20 degrees C and 10 degrees C, and the variations in their electrochemical and microstructural characteristics were analyzed according to the initial microstructures When the MEAs were prepared by spraying catalyst inks on polymer membranes no significant micro structural changes were observed In the case of two supplied MEAs void formations at the electrolyte/electrode interface or vertical cracks within the catalyst layers were observed after 120 F-T cycles Void formation seems to be responsible for performance degradation as a result of ohmic loss, but the effect of cracks in the catalyst layers was not confirmed In 120 F-T cycles activation overpotentials and concentration overpotentials did not increase significantly for any of the MEAs even although gradual decreases in the electrochemically active surface area of the platinum catalysts and changes in the porous structure were observed (C) 2010 Professor T Nejat Veziroglu Published by Elsevier Ltd All rights reserved
Keywords: MEMBRANE-ELECTRODE ASSEMBLIES; FUEL-CELLS; PHYSICAL DEGRADATION; REPETITIVELY BROUGHT; WATER REMOVAL; TEMPERATURES; OPERATION; STARTUP; MODEL